Lease or borrow? The case of small equipment contracts - Schallheim, James; Zhang, Xiaodi (Journal of Corporate Finance, 2026)
Small leases and loans are excellent contracts to study the impact of information costs on the contract choice. Using a specially constructed dataset, we can directly compare the costs of leasing to borrowing for small firms. With a 15% average yield in our overall sample, we show that leases average about 12.5% while loans average 24%. After matching paired-samples of true leases and loans and correcting for selection bias, the differential is smaller but remains significant, while true and non-true leases show very little difference in yields. In our unique time series analysis, the average lease yields are significantly related to proxies for macroeconomic risk and demand factors. In sum, we reject the hypothesis that leasing is a more costly form of financing than “equivalent” borrowing and there are reasonable economic factors, related to enhanced collateral rights, that reduce information costs and account for the pricing differentials.